2011
DOI: 10.1159/000333284
|View full text |Cite
|
Sign up to set email alerts
|

The Brainstem Is at High Risk for Recurrent Noncardioembolic Cerebral Infarction in Association with Diabetes Mellitus: A Hospital-Based Study

Abstract: The goals of the study were to investigate the importance of brainstem infarction (BSI) in recurrent noncardioembolic ischemic stroke and to examine the relevant clinical background. Data were retrospectively reviewed for 655 consecutive patients with acute noncardioembolic infarction who were admitted to our hospital from January 2004 to August 2010. The patients were divided into first-stroke (n = 592) and recurrent-stroke (n = 63) groups. Acute infarcted lesions were explored on MRI, and clinical background… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The main risks of diabetes are chronic complications caused by chronic hyperglycemia, and some of the most important complications are vascular complications (3,6). It is reported that 75% of diabetic patients worldwide succumbed to diabetic vascular complication-associate mortality, and this mortality rate ranks as the second highest of total causes of diabetes-associated mortality (7,23).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The main risks of diabetes are chronic complications caused by chronic hyperglycemia, and some of the most important complications are vascular complications (3,6). It is reported that 75% of diabetic patients worldwide succumbed to diabetic vascular complication-associate mortality, and this mortality rate ranks as the second highest of total causes of diabetes-associated mortality (7,23).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic cerebrovascular disease is mainly caused by diabetic cerebral infarction, which accounts for 85% of diabetic cerebrovascular disease (8,25). The prevalence of the diabetic vascular disease rate increases with increasing duration of diabetes, ischemic lesions rather than hemorrhagic lesions, particularly in lacunar infarction, and due to repeated relapse of the disease, therefore, the prevention and cure of cerebral infarction is key to reducing diabetes morbidity rates (5,6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The candidate variables that were entered into the multivariate analysis were based on newly prior published, traditionally or clinically associated with stroke (mainly focused on stroke recurrence), or P<0.10 in the univariate analysis. After a selection of all the variables (detailed in Text S2 ), the variables entered into the multivariate analysis were: age, gender, education status received, tobacco use, alcohol consumption, systolic and diastolic pressure at baseline and discharge [ 21 ], BMI and waist circumference [ 22 ], history of coronary heart disease, history of hypertension and history of family stroke [ 22 , 23 ], history of diabetes, ischemic stroke subtypes [ 24 ], OCSP subtypes [ 25 ], HOMA [ 26 ], uric acid [ 27 ], homocysteine [ 28 ], creatinine [ 29 ], high density lipoprotein [ 29 ], low density lipoprotein [ 22 ], triglyceride and cholesterol [ 22 ], FPG, medication therapy (antithrombotic, antihypertensive and lipid-lowering medications) during hospitalization and medication adherence (antithrombotic, antihypertensive and lipid-lowering medications) during follow-up. In the multivariate analysis, gender, tobacco use, alcohol intake, family history of stroke, past medical history of hypertension and coronary heart disease, TOAST and OCSP subtypes, medications’ information, and HbA1c were entered as categorical variables.…”
Section: Methodsmentioning
confidence: 99%